Shifting Paradigms in Translanguaging: A Scientometric Analysis of Research Trends and Trajectories - Lalu Nurul Yaqin; James Mclellan; Najib Noorashid (Studies in English Language and Education, 2025)
Over the past decade, numerous papers have documented translanguaging studies, significantly contributing to the shifting paradigm in this research area. Nevertheless, no comprehensive bibliometric analysis has been conducted on the landscape of translanguaging research to uncover the prominent areas and potential future directions. This study focuses on articles from the Scopus database published from 2014 to 2023 with the search keyword "translanguaging." The identified retrieval data (2213 entries) was used to analyze the publication authors, affiliations, source journals, countries, times cited, citation networks, and keyword co-occurrences to uncover the intellectual structure and dynamic progress of translanguaging studies. The data was analyzed and visualized using the Bibliometrix R package and VOSviewer. The results revealed that there has been a steady and continuous growth in the number of publications on translanguaging over the past decade. The USA and the UK are leading countries in translanguaging publications and citations. The shifting themes of translanguaging from 2014 to 2020 focus on language-integrated learning and teacher education. However, from 2021 to 2023, research has risen on various educational and sociolinguistic subjects, including multilingual education, ESL, literacy, equity, classroom interaction, language teaching, home language pedagogy, decoloniality, mobility, and social justice. Further research is needed to explore the influence of technology on translanguaging practices and the capacity of artificial intelligence to improve multilingual communication.